PERCENTAGE OF CD4+ AND CD8+ T-LYMPHOCYTES IN BLOOD OF TUBERCULOSIS PATIENTS - Afzal, Nadeem; Javed, Khursheed; Zaman, Saleem -uz-; Mumtaz, Asim; Hussain, Shahid; Tahir, Romeeza; Ullah, Ikram; Akram, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tuberculosis is a fatal infectious disease, mainly caused by Mycobacterium tuberculosis. Spread of TB is controlled by cell-mediated immunity. Purpose of this study was to determine CD4+ and CD8+ T cell percentages in TB patients. Methods: 77 subjects consisted of 39 patients of active tuberculosis and 37 normal healthy individuals were recruited for the study. Among patients, 27 were at different stages of anti-tuberculous therapy while rests of the patients were not taking treatment. Sixteen patients were sputum positive for AFB while other patients were sputum negative for AFB. T cells percentages were determined by flow cytometer. Results: In TB patients CD4+ and CD8+ T cells percentages were 34.4±9.8 and 32.0±9.8 while in controls these were 37.1±6.9 and 30.2±7.2 respectively but the difference was statistically insignificant. CD4+ T cell percentage in newly diagnosed TB patients was 28.8±8.7 while it was 37.9±8.9 in TB patients who were on therapy and difference was statistically significant whereas difference in CD8+ T-cell percentages was statistically insignificant. A negative correlation between CD8+ Tcells percentage and the duration of ATT was found. Conclusion: CD4+ and CD8+ T-cells percentages may help to find out the immune status of TB patients before and after the completion of ATT. Keywords: TB, CD4+, CD8+, ATT, AFB